Financial Management Concepts: A Review - Sukenti, Siti (ADMAN: Journal of Contemporary Administration and Management, 2023)
Effective and functional financial management can be found in financial management. Financial management is a financial management process that organises financial activities from planning, implementation and control to financial accountability. However, when it comes to educational institutions, the impact is quite significant. This research aims to find out the definition, principles and concepts of return assessment in financial management. This research is literature research, and the data used is secondary data from various literatures. Qualitative descriptive method is used to assess the data obtained. Based on the description of the findings, financial management can be interpreted as business activities related to the acquisition, use and management of company funds to achieve the company's main objectives. Good financial management is certainly needed. The need for financial management can be concluded as the need to identify the objectives that must be met, the right choice is the one that advances the company's goals; usually, the purpose of financial management choices is to maximise the company.